Pengaruh Praktik Kerja Industri, Informasi Dunia Kerja Dan Status Sosial Ekonomi Orang Tua Terhadap Kesiapan Kerja Siswa Smk - Talitha Nathaniela Khairunnisa; Novi Trisnawati (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Student's work readiness plays a vital role in navigating a job market that is progressively becoming more competitive. The study investigates the impact of industrial work practices, access to job market information, and parents’ social status on the job readiness of students majoring in Office Administration and Business Management (OTKP) at SMKN 2 Buduran for the academic year 2023/2024. A purposive sampling technique was used, and the number of students sampled in this study was 74, using a saturated sampling technique. The analytical framework employed a combination of Multiple Linear Regression Test, conducted with the aid of SPSS IBM 25 software. The findings reveal that industrial work practices and access to job market information demonstrably exert a statistically significant positive influence on job readiness, whereas parent’s social status does not appear to significantly impact on job readiness. Moreover, the analysis suggests that the interaction between industrial work practices, access to job market information, and parents’ social status also contribute positively on job readiness. The findings of this research are anticipated to offer a more comprehensive insight to stakeholders such as educational institutions, industries, and government, enabling them to develop education and training that are both more efficient and inclusive, better equipped to address the challenges of a rapidly evolving and competitive job market.